Zinc-nickel plating bath and plating method using said bath
The zinc-nickel plating bath with a pH of 3.5 to 6.9 and cumylphenol anionic surfactants and amine chelating agents addresses inefficiencies in current solutions, providing high-speed plating with a stable, glossy, and burn-resistant zinc-nickel film.
Patent Information
- Application Number
- JP2021566885
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-23
- Filing Date
- 2020-11-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-11-05
AI Technical Summary
Existing zinc-nickel alloy plating solutions face issues with poor current efficiency, slow plating speed, film roughness, and nickel hydroxide deposition on the cathode, particularly in weakly acidic chloride baths, leading to potential burning and loss of luster.
A zinc-nickel plating bath with a pH range of 3.5 to 6.9, using cumylphenol anionic surfactants and amine chelating agents, along with zinc, nickel, and chloride ions, to maintain high-speed plating while preventing nickel hydroxide deposition and burning.
The solution achieves high-speed plating with a stable, dense, and glossy zinc-nickel film resistant to nickel hydroxide deposition and burning, ensuring consistent film quality.
Smart Images

Figure 0007605484000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a zinc-nickel plating bath, an electrolytic zinc-nickel plating bath which can be used as a general surface treatment for preventing corrosion, which is resistant to burning and in which nickel hydroxide is resistant to deposition on the cathode, and a plating method using said bath. [Background technology]
[0002] It is well known that zinc-nickel alloy plating has excellent corrosion resistance. This zinc-nickel alloy plating is usually performed by using an alkaline or weakly acidic plating solution containing zinc ions and nickel ions, and applying a current between the cathode and the anode to plate the cathode with the zinc-nickel alloy on the surface of the cathode. Among these, an alkaline plating solution (bath) is used for zinc-nickel alloy plating on automobile parts, etc., but there are problems with poor current efficiency and slow plating speed. On the other hand, the use of a weakly acidic plating solution (bath) has the advantage of good current efficiency and fast plating speed, but it has been pointed out that the proportion of nickel in the film changes significantly when the current density during plating changes (Patent Document 1). To solve this problem, an acidic zinc-nickel alloy electroplating solution has been proposed that contains (1) zinc ions, (2) nickel ions, (3) conductive salts, (4) pH buffers, and (5) an amine compound represented by the formula H2N-R1-R2 (Patent Document 1). Furthermore, the use of a weakly acidic plating solution (bath) causes the following problems. For example, when high-speed plating is performed using a weakly acidic plating solution (chloride bath) containing potassium chloride as a conductive salt as a stationary bath, scorching (the phenomenon in which the plating film becomes rough, coarse, and loses luster) is likely to occur. In addition, if the amount of pH buffer is insufficient or the stirring is uneven, problems occur in which nickel hydroxide precipitates on the cathode (insufficient current flow) and adheres to the surface of the plated object. In contrast, when plating is performed using a weakly acidic plating solution (eclectic bath) containing potassium chloride (conductive salt) and ammonium chloride (buffer) as a barrel bath (the plated object is placed in a basket and placed in the plating solution (eclectic bath) and rotated during plating), problems occur in which nickel hydroxide precipitates on the cathode and adheres to the surface of the plated object. At the same time, scorching may occur. On the other hand, Patent Document 2 proposes an acidic zinc plating bath containing a conductive salt, metallic zinc, and a brightener, with the brightener containing at least one cumylphenol-based anionic surfactant as a component, as an acidic zinc plating bath with improved stability over time even at high temperatures of 30 to 50° C. However, Patent Document 2 does not mention an acidic zinc-nickel alloy electroplating solution at all. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] WO2014 / 157105A1 [Patent Document 2] WO2010 / 055917A1 Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide an electrolytic zinc-nickel plating bath which is less prone to burning and which is less prone to depositing nickel hydroxide on the cathode. Another object of the present invention is to provide a method for electrolytic zinc-nickel plating. [Means for solving the problem]
[0005] The present invention was made based on the finding that the above problems can be efficiently solved by adjusting the pH of a zinc-nickel plating bath to the range of 3.5 to 6.9 and using a cumylphenol-based anionic surfactant and an amine-based chelating agent in combination with zinc ions, nickel ions, and chloride ions. That is, the present invention has the following aspects. 1. A zinc-nickel plating bath, characterized in that the pH of the plating bath is 3.5 to 6.9, and the zinc-nickel plating bath contains zinc ions, nickel ions, chloride ions, a cumylphenol-based anionic surfactant, and an amine-based chelating agent. 2. The zinc-nickel plating bath according to the above item 1, wherein the cumylphenol-based anionic surfactant is a sulfonate formed by adding cumylphenol to ethylene oxide, propylene oxide or a block copolymer of ethylene oxide and propylene oxide. 3. The zinc-nickel plating bath according to 1 or 2 above, wherein the amine-based chelating agent is at least one member selected from the group consisting of alkyleneamine compounds having 1 to 12 carbon atoms, their ethylene oxide adducts, and their propylene oxide adducts. 4. The zinc-nickel plating bath according to any one of 1 to 3 above, wherein the pH of the plating bath is 4.5 to 6.0. 5. The zinc-nickel plating bath according to any one of the above items 1 to 4, which contains an aromatic carboxylic acid and / or a salt thereof. 6. The zinc-nickel plating bath according to 5 above, wherein the aromatic carboxylic acid and / or its salt is benzoic acid, a benzoate, or a combination thereof.
[0006] 7. The zinc-nickel plating bath according to any one of the above items 1 to 6, which contains an aromatic aldehyde and / or an aromatic ketone. 8. The zinc-nickel plating bath according to the above item 7, wherein the aromatic aldehyde and aromatic ketone are O-chlorobenzaldehyde and benzalacetone, respectively. 9. The zinc-nickel plating bath according to any one of the above items 1 to 8, which contains at least one selected from the group consisting of ammonia, ammonium salts, acetic acid, acetates, boric acid and borates. 10. The zinc-nickel plating bath according to any one of items 1 to 9 above, which does not contain sulfate ions. 11. A plating method comprising using a zinc-nickel plating bath according to any one of items 1 to 10 above to plate an object to be plated, the zinc-nickel plating being performed on the object to be plated as a cathode and zinc, nickel or both of these as an anode. 12. A plating method comprising using a body to be plated as a cathode, zinc and nickel as anodes, placing a part or all of the zinc anode in an anode chamber separated by an ion exchange diaphragm, and applying zinc-nickel plating to the body to be plated using the zinc-nickel plating bath according to any one of items 1 to 10 above. Effect of the Invention
[0007] The plating bath of the present invention is a weakly acidic plating solution (chloride bath), and therefore maintains the advantage of being able to perform high-speed plating, while exhibiting the excellent effects of making the resulting zinc-nickel coating less susceptible to burning and suppressing the phenomenon of nickel hydroxide depositing and adhering to the cathode during electroplating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The electrolytic zinc-nickel plating bath of the present invention is set to a pH of 3.5 to 6.9 in order to make it a weakly acidic bath. A chloride bath is most preferable as such a weakly acidic bath. The pH of the plating bath is preferably 4.5 to 6.0, and most preferably 5.2 to 5.8. The pH of the plating bath can be easily adjusted using hydrochloric acid, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous ammonia solution, an aqueous sodium carbonate solution, an aqueous potassium carbonate solution, acetic acid, an aqueous sodium acetate solution, an aqueous potassium acetate solution, or the like. The plating bath of the present invention contains zinc ions, nickel ions, chloride ions (Cl-), a cumylphenol-based anionic surfactant, and an amine-based chelating agent as essential components. The zinc ions are provided from a water-soluble zinc salt, and the water-soluble zinc salt is preferably zinc chloride. The concentration of the water-soluble zinc salt is preferably 40 to 130 g / L, and more preferably 60 to 110 g / L. The nickel ions are provided from a water-soluble nickel salt, and the water-soluble nickel salt is preferably nickel chloride. The concentration of the nickel chloride hexahydrate is preferably 70 to 150 g / L, and more preferably 75 to 120 g / L. The chloride ions are provided by the zinc chloride and nickel chloride, but also by other water-soluble chlorides added to the plating bath. The amount of chloride ions is the total amount of chloride ions provided by the water-soluble chlorides in the plating bath. The concentration is preferably 100 to 300 g / L. More preferably, the concentration is 120 to 240 g / L.
[0009] The cumylphenol-based anionic surfactant may be a sulfonate obtained by adding 3 to 65 moles, preferably 8 to 62 moles, of ethylene oxide and / or propylene oxide to cumylphenol. Examples of the sulfonate include potassium salts, sodium salts, and amine salts. Specifically, examples include polyoxyethylene p-cumylphenyl ether sulfate sodium salt (EO addition mole number 3 to 65 moles, preferably 8 to 62 moles). The concentration of the sulfonate obtained by adding cumylphenol to ethylene oxide and / or propylene oxide in the plating bath is preferably 0.1 to 10 g / L, and more preferably 0.2 to 5 g / L. These cumylphenol-based anionic surfactants are readily available on the market, for example, as Newcol CMP-4-SN (4 moles of EO added), CMP-11-SN (11 moles of EO added), CMP-40-SN (40 moles of EO added), CMP-60-SN (60 moles of EO added) and the like, all of which are manufactured by Nippon Nyukazai Co., Ltd.
[0010] Examples of the amine-based chelating agent include alkyleneamine compounds such as ethylenediamine, diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, ethylene oxide adducts and propylene oxide adducts of the alkyleneamines; aminoalcohols such as N-(2-aminoethyl)ethanolamine and 2-hydroxyethylaminopropylamine; poly(hydroxyalkyl)alkylenediamines such as N-2(-hydroxyethyl)-N,N',N'-triethylethylenediamine, N,N'-di(2-hydroxyethyl)-N,N'-diethylethylenediamine, N,N,N',N'-tetrakis(2-hydroxyethyl)propylenediamine, and N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine; poly(alkyleneimines) obtained from ethyleneimine, 1,2-propyleneimine, and the like, and poly(alkyleneamines) or poly(aminoalcohols) obtained from ethylenediamine, triethylenetetramine, ethanolamine, diethanolamine, and the like. Among these, alkyleneamine compounds having 1 to 12 carbon atoms (preferably 2 to 10 carbon atoms) and 2 to 7 nitrogen atoms (preferably 2 to 6 nitrogen atoms), and their ethylene oxide adducts and propylene oxide adducts are preferred. These amine chelating agents may be used alone or in combination of two or more. The concentration of the amine chelating agent in the plating bath is preferably 0.5 to 50 g / L, more preferably 1 to 5 g / L.
[0011] The plating bath of the present invention may contain one or more conductive salts. By using a conductive salt, the voltage during current application can be reduced and the current efficiency can be improved. Examples of conductive salts used in the present invention include chlorides, sulfates, and carbonates. Among them, it is preferable to use at least one chloride selected from potassium chloride, ammonium chloride, and sodium chloride. In particular, potassium chloride and ammonium chloride are preferably used alone or in combination. The concentration of potassium chloride is preferably 150 to 250 g / L when used alone, and the concentration of ammonium chloride is preferably 150 to 300 g / L when used alone. When potassium chloride and ammonium chloride are used in combination, potassium chloride is preferably 70 to 200 g / L, and ammonium chloride is preferably 15 to 150 g / L. Ammonium chloride also has an effect as a buffering agent. When ammonium chloride is not used, it is preferable to use ammonia, ammonium salts, boric acid or boric acid salts, acetic acid, potassium acetate, sodium acetate, and other acetates as a buffering agent. The total concentration of boric acid and / or boric acid salts is preferably 15 to 90 g / L. The total concentration of acetic acid and / or acetate is preferably 5 to 140 g / L, more preferably 7 to 140 g / L, and even more preferably 8 to 120 g / L. Even when ammonium chloride is used, these buffers can be used appropriately.
[0012] When densification and gloss of the plating film are required, the plating bath of the present invention preferably contains an aromatic aldehyde having 7 to 10 carbon atoms or an aromatic ketone having 8 to 14 carbon atoms. Examples of aromatic aldehydes include o-carboxybenzaldehyde, benzaldehyde, o-chlorobenzaldehyde, p-tolualdehyde, anisaldehyde, p-dimethylaminobenzaldehyde, and terephthalaldehyde. Examples of aromatic ketones include benzalacetone, benzophenone, acetophenone, and terephthaloylbenzyl chloride. Particularly preferred compounds are benzalacetone and o-chlorobenzaldehyde. The respective bath concentrations are preferably 0.1 to 20 mg / L, more preferably 0.3 to 10 mg / L. The balance of the plating bath of the present invention is water.
[0013] The plating method using the zinc-nickel plating bath of the present invention is electroplating, which can be carried out by using a direct current or a pulse current. The bath temperature is usually in the range of 25 to 50°C, preferably in the range of 30 to 45°C. The electrolysis is preferably performed under the condition of a current density usually in the range of 0.1 to 15 A / dm2, preferably in the range of 0.5 to 10 A / dm2. When plating is performed, it is preferable to agitate the solution by air blowing or jet flow. This can further increase the current density. The anode is preferably a zinc plate, a nickel plate, a zinc ball, a nickel chip, or the like. The cathode is a metal article to be coated with the zinc-nickel plating film of the present invention. The metal article may be an electrically conductive article made of various metals such as iron, nickel, copper, or alloys thereof, or aluminum or alloys thereof that have been subjected to zinc substitution treatment. The shape of the metal article may be any shape, such as a flat plate or a complicated shape, for example, fasteners such as bolts and nuts, or cast parts such as brake calipers. In the present invention, furthermore, the object to be plated can be used as the cathode, zinc and nickel as the anodes, and part or all of the zinc anode can be placed in an anode chamber separated by an ion exchange diaphragm, and the object to be plated can be plated with zinc-nickel plating using the zinc-nickel plating bath. This method has the advantage that the increase in metal concentration (especially zinc concentration) in the plating solution that accompanies operation can be suppressed and controlled, resulting in a plated film of stable quality.
[0014] The nickel co-deposition rate in the zinc-nickel plating film obtained using the electrolytic zinc-nickel plating bath of the present invention is preferably 5 to 18% by weight, more preferably 10 to 18% by weight, and most preferably 12 to 15% by weight. The higher the nickel co-deposition rate, the better the corrosion resistance, and the most preferable nickel co-deposition rate provides the best corrosion resistance. The remainder is preferably zinc. The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples in any way. EXAMPLES
[0015] Example 1 A plating bath (1 liter) was prepared by mixing and dissolving 73 g / L of zinc chloride (35 g / L as zinc concentration), 89 g / L of nickel chloride hexahydrate (22 g / L as nickel concentration), 180 g / L of potassium chloride (170 g / L as total chlorine concentration), 30 g / L of ammonium chloride, 0.25 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (40 moles of EO added: Newcol CMP-40-SN), 6 mg / L of benzalacetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate in water and adjusting the pH to 5.4 using hydrochloric acid. Next, the iron plate was pretreated by the steps of alkaline degreasing, water washing, pickling, water washing, alkaline electrolytic cleaning, water washing, hydrochloric acid activation, and water washing, and used as a cathode. A nickel plate was used as an anode, and the bath temperature was set at 35°C and the cathode current density was set at 4A / dm2 from a DC power source. 2 The plating bath was stirred at a rotation speed of 1200 rpm using a regular stirring bar of φ8×30 mm and a magnetic stirrer. The iron plate is a long panel for Hull cell testing, measuring 65 mm in length, 200 mm in width and 0.5 mm in thickness, and the nickel plate is a plate measuring 65 mm in length, 65 mm in width and 2 mm in thickness. In this example, a plating test similar to the Hull Cell test was carried out, and the nickel co-deposition rate (%) of the zinc-nickel plating film, the film thickness distribution, the deposition of nickel hydroxide at the cathode, and the scorching and appearance (Hul Cell appearance) of the zinc-nickel plating film were evaluated by the following methods. The evaluation results are shown in Table 1.
[0016] (Method of measuring Ni co-deposition rate (%) and thickness) The nickel co-deposition rate (%) and thickness of the plating film were measured using an X-ray fluorescence analyzer (Microelement Monitor SEA5120, manufactured by SII NanoTechnology, Inc.). (Cathodic Deposition of Nickel Hydroxide) The cathode surface was visually observed after the zinc-nickel plating process was completed, and the deposition of nickel hydroxide on the cathode was evaluated according to the following criteria: If the evaluation in the Hull Cell test is A or B, nickel hydroxide will not deposit on the object to be plated or on the cathode (dangler) of the barrel plating device when plating is actually performed using the object. A: The deposition width is less than 3 mm from the left end (high current side) of the Hull Cell test panel (good). B: The deposition width is less than 6 mm from the left end (high current side) of the Hull Cell test panel (within the allowable range). C: Deposition width is 6 mm or more from the left end (high current side) of the Hull Cell test panel (unusable) (Zinc-nickel plating film burnt) The occurrence of scorching on the zinc-nickel plating film at the end of the zinc-nickel plating process was evaluated according to the following criteria. If the evaluation in the Hull Cell test is A or B, when plating is actually performed using an item, scorching will not occur on the plated object. A: The burn width is less than 6 mm from the left end (high current side) of the Hull Cell test panel (good). B: The burn width is less than 9 mm from the left end (high current side) of the Hull Cell test panel (within the allowable range). C: Burn width is 9mm or more from the left end (high current side) of the Hull Cell test panel (unusable) (Appearance of zinc-nickel plating film (Hull cell appearance)) The hull cell appearance of the zinc-nickel plating film after the zinc-nickel plating process was evaluated according to the following criteria. A: Hull cell test panel, 3mm from the left end (high current side) to the right, no scorching, clouding or stains (very good appearance) B: Hull cell test panel, 6 mm from the left end (high current side) to the right, no scorching, clouding or stains (good appearance) C: Hull cell test panel, no scorching, clouding or stains on the right side from 9mm from the left end (high current side) (within the acceptable range) D: Hull cell test panel has a hazy appearance and light stains on the entire panel (unusable). E: Hull cell test panel has dark cloudiness or stains on the entire panel (unusable)
[0017] Example 2 A plating bath (1 liter) was prepared by mixing and dissolving 73 g / L of zinc chloride (35 g / L as zinc concentration), 89 g / L of nickel chloride hexahydrate (22 g / L as nickel concentration), 180 g / L of potassium chloride (170 g / L of total chlorine concentration), 30 g / L of ammonium chloride, 1 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (60 moles of EO added: Newcol CMP-60-SN), 6 mg / L of benzalacetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate in water and adjusting the pH to 5.4 using hydrochloric acid. Next, plating was performed under the same conditions as in Example 1 using the same cathode and anode as in Example 1, and the deposition of nickel hydroxide at the cathode, and the scorching and appearance (hull cell appearance) of the zinc-nickel plating film were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0018] Example 3 A plating bath (1 liter) was prepared by mixing and dissolving 73 g / L of zinc chloride (35 g / L as zinc concentration), 89 g / L of nickel chloride hexahydrate (22 g / L as nickel concentration), 180 g / L of potassium chloride (170 g / L of total chlorine concentration), 30 g / L of ammonium chloride, 1 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (11 moles of EO added: New Coal CMP-11-SN), 6 mg / L of benzalacetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate in water and adjusting the pH to 5.4 using hydrochloric acid. Next, plating was performed under the same conditions as in Example 1 using the same cathode and anode as in Example 1, and the deposition of nickel hydroxide at the cathode, and the scorching and appearance (hull cell appearance) of the zinc-nickel plating film were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0019] Example 4 A plating bath (1 liter) was prepared by mixing and dissolving 73 g / L of zinc chloride (zinc concentration: 35 g / L), 89 g / L of nickel chloride hexahydrate (nickel concentration: 22 g / L), 180 g / L of potassium chloride (total chlorine concentration: 170 g / L), 30 g / L of ammonium chloride, 1 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (EO added moles: 20 moles: Newcol CMP-20-SN), 6 mg / L of benzalacetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate in water and adjusting the pH to 5.4 using hydrochloric acid. Next, plating was performed under the same conditions as in Example 1 using the same cathode and anode as in Example 1, and the deposition of nickel hydroxide at the cathode, and the scorching and appearance (hull cell appearance) of the zinc-nickel plating film were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0020] Example 5 A plating bath (1 liter) was prepared by mixing and dissolving 73 g / L of zinc chloride (zinc concentration of 35 g / L), 89 g / L of nickel chloride hexahydrate (nickel concentration of 22 g / L), 220 g / L of potassium chloride (total chlorine concentration of 170 g / L), 1 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (EO added moles: 11 moles: Newcol CMP-11-SN) in water and adjusting the pH to 5.4 using hydrochloric acid. Next, plating was performed under the same conditions as in Example 1 using the same cathode and anode as in Example 1, and the deposition of nickel hydroxide at the cathode, and the scorching and appearance (hull cell appearance) of the zinc-nickel plating film were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0021] Comparative Example 1 73 g / L of zinc chloride (zinc concentration 35 g / L), 89 g / L of nickel chloride hexahydrate (nickel concentration 22 g / L), 180 g / L of potassium chloride (total chlorine concentration 170 g / L), 30 g / L of ammonium chloride, 4 g / L of nonylphenol-based nonionic surfactant (EO added moles 30 added) (Pelletex 1245S manufactured by Miyoshi Oil Co., Ltd.), 6 mg / L of benzal acetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate were mixed and dissolved in water, and the pH was adjusted to 5.4 using hydrochloric acid to prepare a plating bath (1 liter). Next, plating was performed under the same conditions as in Example 1 using the same cathode and anode as in Example 1, and the deposition of nickel hydroxide at the cathode, and the scorching and appearance (hull cell appearance) of the zinc-nickel plating film were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0022] Comparative Example 2 A plating bath (1 liter) was prepared by mixing and dissolving 73 g / L of zinc chloride (35 g / L as zinc concentration), 89 g / L of nickel chloride hexahydrate (22 g / L as nickel concentration), 180 g / L of potassium chloride (170 g / L of total chlorine concentration), 30 g / L of ammonium chloride, 4 g / L of polyoxyethylene alkylphenol type nonionic surfactant (10 moles of EO added) (Brownon BEO-10 manufactured by Aoki Oil & Fat Co., Ltd.), 6 mg / L of benzal acetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate in water and adjusting the pH to 5.4 using hydrochloric acid. Next, plating was performed under the same conditions as in Example 1 using the same cathode and anode as in Example 1, and the deposition of nickel hydroxide at the cathode, and the scorching and appearance (hull cell appearance) of the zinc-nickel plating film were evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0023] Comparative Example 3 The plating bath (1 liter) was prepared in the same manner as in Example 1, except that 4 g / L of a cumylphenol-based nonionic surfactant (11 moles of EO added: Newcol CMP-11 manufactured by Nippon Nyukazai Co., Ltd.), 4 g / L of a polyoxyethylene alkylphenol-based nonionic surfactant (16 moles of EO added: Brownon KTSP-1604P manufactured by Aoki Oil & Fat Co., Ltd.), or 4 g / L of a polyoxyethylene alkylphenol-based nonionic surfactant (2 moles of EO added: Brownon N-502 manufactured by Aoki Oil & Fat Co., Ltd.) was used instead of 0.25 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (40 moles of EO added: Newcol CMP-40-SN) in Example 1. However, since these nonionic surfactants did not dissolve in the plating bath, plating tests similar to the Hull Cell test were not performed.
[0024] Table 1. Measurement results of the Ni co-deposition rate (%) of the zinc-nickel plating film, film thickness distribution, deposition of nickel hydroxide at the cathode, and scorching and appearance (hull cell appearance) of the zinc-nickel plating film TIFF0007605484000001.tif109160
[0025] As is clear from the results in Table 1, according to the present invention, it is possible to prevent the deposition of nickel hydroxide at the cathode, suppress the occurrence of scorching of the zinc-nickel plating film, and obtain a zinc-nickel plating film with excellent appearance (Examples 1 to 5). In contrast, in Comparative Examples 1 and 2, which used conventional surfactants other than cumylphenol-based anionic surfactants, it was found that the three requirements of preventing nickel hydroxide deposition at the cathode, suppressing scorching of the zinc-nickel plating film, and providing a zinc-nickel plating film with excellent appearance could not be simultaneously achieved.
[0026] Example 6 A plating bath (15 liters) was prepared by mixing and dissolving 73 g / L of zinc chloride (35 g / L as zinc concentration), 89 g / L of nickel chloride hexahydrate (22 g / L as nickel concentration), 180 g / L of potassium chloride (170 g / L of total chlorine concentration), 30 g / L of ammonium chloride, 1 g / L of polyoxyethylene p-cumylphenyl ether sulfate sodium salt (11 moles of EO added: New Coal CMP-11-SN), 6 mg / L of benzalacetone, 2.5 g / L of diethylenetriamine, 1.5 g / L of sodium benzoate, and 90 g / L of potassium acetate in water and adjusting the pH to 5.4 using hydrochloric acid. Next, the iron bolts were pretreated by the following steps: alkaline degreasing, water washing, pickling, water washing, alkaline electrolytic cleaning, water washing, hydrochloric acid activation, and water washing. Zinc and nickel plates were used as anodes, and the bath temperature was 35°C. The cathode current density was 0.75 A / dm2 from a DC power source. 2 The plating was carried out for 45 minutes at 4 to 6 rpm using an autogilder. The iron bolts are M8 x 55 size hexagonal bolts (half-threaded type), and the zinc and nickel plates are 300 mm long, 100 mm wide and 20 mm thick, while the nickel plates are 300 mm long, 150 mm wide and 15 mm thick. In this example, the nickel co-deposition rate (%) of the zinc-nickel plating film, the film thickness, the deposition of nickel hydroxide on the hexagonal bolt and the autoguild cathode (dangler), and the scorching and plating appearance of the zinc-nickel plating film were evaluated using the methods of Example 1. evaluation The measurement results at the center of the width across the head of a hexagonal bolt showed a nickel co-deposition rate of 14%, a film thickness of 10 μm, There was no deposition of nickel hydroxide on the hexagonal bolt or the autoguild cathode (dangler), and the zinc-nickel alloy plating film had a good appearance without any scorching, clouding or stains.
Claims
1. A zinc-nickel plating bath, characterized in that the pH of the plating bath is 3.5 to 6.9, and the zinc-nickel plating bath contains zinc ions, nickel ions, chloride ions, a cumylphenol-based anionic surfactant, and an amine-based chelating agent.
2. 2. The zinc-nickel plating bath according to claim 1, wherein the cumylphenol-based anionic surfactant is a sulfonate obtained by adding cumylphenol to ethylene oxide, propylene oxide or a block copolymer of ethylene oxide and propylene oxide.
3. 3. The zinc-nickel plating bath according to claim 1, wherein the amine-based chelating agent is at least one member selected from the group consisting of alkyleneamine compounds having 1 to 12 carbon atoms, their ethylene oxide adducts, and their propylene oxide adducts.
4. The zinc-nickel plating bath according to any one of claims 1 to 3, wherein the pH of the plating bath is 4.5 to 6.
0.
5. The zinc-nickel plating bath according to any one of claims 1 to 4, further comprising an aromatic carboxylic acid and / or a salt thereof.
6. 6. The zinc-nickel plating bath according to claim 5, wherein the aromatic carboxylic acid and / or its salt is benzoic acid, a benzoate, or a combination thereof.
7. The zinc-nickel plating bath according to any one of claims 1 to 6, further comprising an aromatic aldehyde and / or an aromatic ketone.
8. 8. The zinc-nickel plating bath according to claim 7, wherein the aromatic aldehyde and aromatic ketone are O-chlorobenzaldehyde and benzalacetone, respectively.
9. The zinc-nickel plating bath according to any one of claims 1 to 8, further comprising at least one selected from the group consisting of ammonia, ammonium salts, acetic acid, acetate salts, boric acid and borates.
10. The zinc-nickel plating bath according to any one of claims 1 to 9, which does not contain sulfate ions.
11. A plating method comprising the steps of: using a substrate as a cathode and zinc, nickel or both of them as an anode; and plating the substrate with zinc-nickel by using the zinc-nickel plating bath according to any one of claims 1 to 10.
12. A plating method comprising the steps of: using a substrate to be plated as a cathode, zinc and nickel as anodes, placing a part or all of the zinc anode in an anode chamber separated by an ion exchange diaphragm; and applying zinc-nickel plating to the substrate to be plated using the zinc-nickel plating bath according to any one of claims 1 to 10.
Citation Information
Patent Citations
Zinc-nickel alloy plating method
JP2007002274A
Additive for acidic zinc alloy plating bath, acidic zinc alloy plating bath and method for producing zinc alloy plated member
JP2016069725A
Acidic zinc and zinc-nickel alloy plating bath compositions and electroplating methods
JP2017538032A
Method for galvanically depositing zinc and zinc alloy coatings from alkaline coating baths with reduced decomposition of organic bath additives
JP2019530800A
JPP6582353B
